INSTITUTIONAL AND ECONOMIC ASPECTS OF THE DEVELOPMENT OF THE SUNFLOWER MARKET (INNOVATIVE ECONOMY, 2025)
Datsenko I.V.  INSTITUTIONAL AND ECONOMIC ASPECTS OF THE DEVELOPMENT OF THE SUNFLOWER MARKETPurpose. The aim of the article is a comprehensive analysis of the institutional and economic aspects of the development of the sunflower market in Ukraine, as well as determining the prospects and directions of its sustainable transformation in the context of global instability and military challenges.Methodology of research. The research methodology is based on a combination of theoretical and applied approaches, which provided a comprehensive analysis of the institutional and economic aspects of the development of the sunflower market. The dialectical method and system analysis were used to identify the relationship between economic and institutional factors, which allowed us to consider the market as a holistic system with a multi-level structure and interaction of the main actors. Economic and statistical methods were used to assess the dynamics of production, exports, price fluctuations and the level of market concentration, which made it possible to trace the key trends in its development. A comparative analysis of international experience was also used, which made it possible to identify ways to adapt leading world practices to Ukrainian conditions.Findings. The results of the study showed that the Ukrainian sunflower market has strategic potential, but its development is limited by institutional and economic factors. Dependence on external markets, high concentration of exports, price instability and imperfect state regulation were identified. The institutional environment is formed under the influence of formal mechanisms (legislation, state policy) and informal factors (market practices, partnerships). The role of state regulatory mechanisms in ensuring market stability in the face of military challenges and global instability was clarified. Export diversification, development of storage and processing infrastructure, and strengthening of institutional support are necessary to ensure market stability. The obtained results create a basis for improving the organizational and economic mechanism and increasing the competitiveness of the sunflower market.Originality. Conceptual approaches to improving the organizational and economic mechanism are proposed, which involve adapting best international practices to Ukrainian conditions in order to increase competitiveness and strengthen food security. It is substantiated that the dominance of crude sunflower oil production hinders the possibility of creating high added value in processing chains. Promising areas of diversification include expanding the production of further processed products - margarines, mayonnaises, food concentrates, protein ingredients, as well as technical oils for the needs of bioenergy and industrial production. At the same time, it is advisable to stimulate domestic demand, which is significantly lower in level compared to the dominant export segment. The growth of the domestic market can act as an additional stabilization tool for producers during periods of external economic and geopolitical upheavals.Practical value. The provisions proposed in the study can be used in the formation of mechanisms for diversifying export flows, improving the regulatory system, and stimulating domestic processing of sunflower products. The application of the outlined approaches will help strengthen institutional support for the agricultural sector, increase the efficiency of the use of production resources, and reduce the industry's sensitivity to external shocks. The obtained results can serve as a practical basis for agricultural enterprises, specialized associations, and government agencies in forming development strategies and strengthening the competitive positions of the Ukrainian sunflower market.Key words: sunflower market, institutional and economic aspects, institutional environment, state regulation, export, food security, agricultural sector, competitiveness, economic development, international experience.
Keywords: sunflower market; institutional and economic aspects; institutional environment; state regulation; export; food security; agricultural sector; competitiveness; international experience; economic development